The CNC Turning Virtual as Teaching and Training Aid of CNC Programming - Bambang Setyo Hari Purwoko (LPPM UNY, 2013)
The study is aimed at (1) describing how the building process of a virtual reality CNC can perceive input and react as a real CNC machine, and (2) showing the results of of the real CNC machine as used as a programming learning media. The study involved 16 students of the Faculty of Engineering as the research subjects. Data collection method was conducted in a span of four months of effective face-to-face class activities. Data collection took place in the CNC lab of the Faculty of Engineering, UNY Results of the study show (1) the students are interested and excited to use the virtual CNC which provides a visual effect of environment of CNC machine in the monitor, actively trying the simulation of numpad virtual in the monitor, inputting data on the panel virtual, and making simulation or execution of the CNC program at CNC Machine Simulator, (2) the students practice to make and execute the CNC programming individually in the classroom or outdoor class. And (3) CNC Virtual can be used as teaching and training media classically (in classroom), individually learning, even E-Iearning.